Polyketides, diketopiperazines and an isochromanone from the marine-derived fungal strain Fusarium graminearum FM1010 from Hawaii. (June 2022) - Uz Zaman, KH Ahammad; Sarotti, Ariel M.; Wu, Xiaohua; DeVine, Lela; Cao, Shugeng
Abstract: The fungal strain Fusarium graminearum FM1010 was isolated from a shallow-water volcanic rock known as "live rock" at the Richardson's Beach, Hilo, Hawaii. Eleven specialised metabolites, including two undescribed diketopiperazines, three undescribed polyketides, and one undescribed isochromanone, along with five known fusarielin derivatives were obtained from F. graminearum FM1010. The structures of the six undescribed compounds were elucidated by extensive analysis of NMR spectroscopy, HRESIMS, chemical reactions, and electronic circular dichroism (ECD) data. Kaneoheoic acids G-I showed mild inhibitory activity against S. aureus with the MIC values in the range of 20–40 μg/mL when assayed in combination with chloramphenicol (half of the MIC, 1 μg/mL), an FDA approved antibiotic. Kaneoheoic acid I exhibited both anti-proliferative activity against ovarian cancer cell line A2780 and TNF-α induced NF-κB inhibitory activity with the IC50 values of 18.52 and 15.86 μM, respectively. Graphical abstract: Eleven specialised metabolites have been obtained from Fusarium graminearum FM1010, which was isolated from a "live rock" in Hawaii. Four compounds showed antibacterial activity against S. aureus . Image 1 Highlights: Six undescribed compounds including 2 uncommon diketopiperazines were identified. Absolute configurations were confirmed by ECD calculation and Marfey's reaction. Compounds 2 –5 showed antibacterial activities when combined with chloramphenicol. Compounds 5 exhibited anti-proliferative activity against ovarian cancer cell line. Compounds 5 also showed TNF-α induced NF-κB inhibitory activity.